Sealing Ability of Nano-fast Cement vs. Mineral Trioxide Aggregate as Retrograde Apical Plugs: An In-vitro Microleakage Study - Moazami, Fariborz; Ghorbani Jahandizi, Negar; Shekouhi, Mohammad Mehdi; Ghahramani, Yasmin (Iranian Endodontic Journal, 2023)
Introduction: Apical surgery aims to eradicate the apical part of the root and the lesion to enhance the healing. The sealing ability of retrograde filling material is an essential factor affecting the success rate of the surgery. Mineral trioxide aggregate (MTA) is the gold standard of retrograde filling materials, with approved sealing capability and biocompatibility. Newly introduced root repair material with an approved antibacterial effect similar to MTA is Nano-fast cement (NFC) which should be investigated for its sealing ability. This study aimed to evaluate the sealing ability of NFC vs. MTA. Materials and Methods: Root apices of 48 single-rooted teeth were resected at 90 degrees and were prepared at 3 mm depth. The teeth were randomly divided into 2 experimental groups (n=21), negative control group (n=3), and positive control group (n= 3). MTA and NFC plugs were condensed as retrograde filling material. The samples were evaluated by a modified fluid filtration device for 1 hour. The measurement was conducted at 24 h, 1, and 3 months. Data were analyzed by Friedman Test and Kruskal-Wallis test. Results: According to the results, NFC at 3-months interval showed the least microleakage, and MTA had the highest at the baseline. However, the results between the two groups were not statistically significant in all intervals. NFC reached the ideal sealing ability within 1 month, which was reached for MTA after 3 months. Conclusions: The results of this in vitro study showed that the microleakage value of NFC is comparable to MTA. In light of current findings, NFC shows characteristics of a suitable calcium silicate-based cement. Further clinical researches are needed to introduce the NFC as retrograde apical plug or for other endodontic applications.